A novel method to calculate the increasing rate of water cut in water flooding oil reservoirs. Issue 3 (4th May 2023) - Zhang, Hongyou; Wang, Yuejie; Wang, Meinan; Deng, Qi; Zhang, Yanhui
ABSTRACT: In this paper, a new method for studying the theoretical water cut increasing rate of water flooding reservoirs is proposed based on the correction of the traditional fractional flow equation. First, the stream tube model was used to solve the saturation distribution field of reverse nine-point injection-production well pattern. Second, through analyzing the saturation results, the linear formula between the average water saturation of the reservoir after water breakthrough and the water saturation at the outlet was established for the first time. Then, based on the linear formula, the traditional fractional flow equation was corrected and a new method was proposed. Finally, the proposed method was applied to Bohai S oilfield to demonstrate its accuracy and practicability. On the one hand, the results show that compared with the traditional fractional flow equation method, the prediction accuracy of the proposed method has increased from 80% to more than 92%. On the other hand, the application of the new method effectively evaluates the development effect of oilfields with high water cut and guides formulation of reasonable adjustment measures.